Podmiotowość, rewolucja demokratyczna,wykorzenienie. Pojęcie hegemonii Antonio Gramsciego w kontekście nowoczesnych przemian władzy - Wróblewski, Michał (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2012)
The aim of this text is to situate the Gramscian theory of hegemony in the context of a philosophical reflection on power. The modern transformation of power is based on three processes: the emergence of a model of power which is focused on subjectivity; a democratic revolution (acquiring of a political identity by a growing number of social groups) and the delegation of power. The main argument of this article is that hegemony is a practice of gaining and maintaining power, which is characteristic of modernity, its practices and institutions. It entails exerting moral, cultural and intellectual authority, by an alliance of dominant groups, over other social groups. The aim of hegemony is to subjugate these groups, not only through coercion, but also through eliciting their consent.